Pengaruh Terpaan Promosi Penjualan Dan Daya Tarik Brand Ambassador Terhadap Minat Beli Produk Kosmetik Wardah - Fahrida Amalia Husna; Muhammad Bayu Widagdo; Nurist Surayya Ulfa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
Wardah as one of the pioneers of cosmetics in Indonesia is experiencing a decline in sales from which previously ranked first to second. Even though Wardah has carried out various marketing communication strategies, namely intensively providing sales promotions and also collaborating with the Korean convert brand ambassador Ayana Jihye Moon. This study aims to determine the influence of sales promotion exposure and Brand Ambassador attractiveness to the Customer Buying Intention of Wardah Cosmetic Products. The theory used in this study is Advertising Exposure Theory by Batra, Myers, and Aaker and Source Attractiveness Theory by McGuire. In determining the sample, this study used a non-probability sampling technique with an accidental sampling technique. The number of samples is 100 people with an age range of 13- 22 years who have been exposed to Wardah's sales promotion and know Wardah's brand ambassador. The results indicated that the variable of sales promotion exposure with interest in buying Wardah cosmetic products had a significance value of 0.814 where the number was more than 0.05 which means it was not significant and it can be argued that sales promotion exposure had no effect on buying interest in Wardah cosmetic products. While the variable of brand ambassador attractiveness with the interest in buying Wardah cosmetic products obtained a significance value of 0.000 where the number is less than 0.05 which means that the brand ambassador attractiveness, influence the customer buying intention of Wardah cosmetic products.